Association between migraine and preeclampsia: A review study - Simbar, M; Karimian, Z (Advances in Nursing & Midwifery, 2009)
Background Preeclampsia is a syndrome specific to pregnancy, resulting in decreased organ perfusion due to vasoconstriction endothelium activation. Migraine is also a benign and recurrent syndrome with headache, nausea and vomiting or other neurological dysfunctions. Some studies suggest that women with migraine are more likely experience preeclampsia. Purpose This study was performed to review literature regarding possible associations between migraine and preeclampsia and to provide an analysis concerning similar mechanisms underlying both of these unknown conditions. Methods Various sources were reviewed in order to collect data on the two conditions and underlying mechanisms involved. Results Although primary mechanisms of both conditions are not clearly known, abnormal platelet activity and altered vascular function have been suggested. Peripheral dysfunction in preeclampsia also occurs in cerebral vessels during migraine attacks. Patients with migraine or with altered gestational blood pressure are similarly influenced by the same drugs and interventions. Conclusion Identifying the risk factors of preeclampsia and predicting them on time can prevent its occurrence. Meanwhile, the association between migraine and preeclampsia may be a key to discover the unknown etiologies of them. Keywords: Pregnancy, Preeclampsia, Migraine.